Human Rights and Persons with Disabilities: Design of Buk-Smart-Logi Learning Media (Technology Smart Books) as an Islamic Education Learning Media Innovation - Ican Mandala (Badan Strategi Kebijakan Hukum, 2022)
The effectiveness of teaching and learning processes, particularly in religious education, heavily relies on the quality of learning media utilized. However, a significant challenge persists related to the absence of inclusive learning systems, thereby hindering the realization of equal access to education as a human right. This observation is drawn from the analysis of inclusive learning media in Indonesian schools. In response, educational institutions must adopt learning media that accommodate individuals with disabilities, enabling all children to study together in integrated settings. To address this gap, the Buk-Smart-Logi (Book Smart Technology) innovation has been introduced, aimed at enhancing student learning outcomes and fostering inclusivity across educational settings in Indonesia. This research employs the Research and Development (R&D) approach using the simplified Borg and Gall model. The study's objectives include assessing the validity of Buk-Smart-Logi media and examining its role in supporting inclusive learning, particularly in Islamic Religious Education. Emphasizing human-friendly design, this media innovation seeks to ensure that education remains accessible to every citizen, including those with disabilities. By enhancing accessibility and inclusivity through innovative learning media, such as Buk-Smart-Logi, the research not only promotes educational equity but also upholds the principles of human rights in education. It underscores the imperative of creating environments where all learners, regardless of ability, can actively participate and benefit from educational opportunities, thereby fostering a more inclusive and supportive educational landscape in Indonesia.